A pilot study of telemedicine for post-operative urological care in children. (December 2014) - Canon, Stephen; Shera, Annashia; Patel, Ashay; Zamilpa, Ismael; Paddack, John; Fisher, Paige L; Smith, Jacob; Hurtt, Robbie
We conducted a retrospective study of paediatric urological surgery patients over a 12-month period. We compared patients followed up by telemedicine with those who had post-operative follow-up on site at the Arkansas Children's Hospital (ACH) in Little Rock. All pre-operative patients living in northwest Arkansas were given the opportunity to use telemedicine from a satellite clinic at Lowell, 328 km from the hospital. Of 61 patients, 10 chose telemedicine and 51 chose to be evaluated at the ACH clinic. All telemedicine visits were completed successfully, but in four cases, the video clarity of the telemedicine images was not sufficient for decision-making, and a digital photograph was sent by email to the physician at the ACH. There were no post-operative surgical complications in either patient group. In the telemedicine group, the median distance to the ACH was 330 km, and the median distance to the remote clinic was 35 km. In the on-site group, the median distance to the ACH was 293 km, which was significantly less ( P  = 0.03). In the on-site group, the median travel time to the ACH was 174 min. If the telemedicine group had driven to the hospital, the median travel time would have been 192 min. Logistic regression showed that for every 37 km increase in distance to ACH, patients had a 111% increase in the odds of receiving telemedicine compared to receiving on-site care (OR = 2.1, 95% CI: 1.0, 4.4). The pilot study supports the use of telemedicine for the post-operative evaluation of paediatric urology surgery patients and suggests that substantial travel distance and time savings can be made.